Learners’ Personalities and Language Learning: A Literature Review - Saarah Nabiilah Octaviani; Jumariati Jumariati; Eka Puteri Elyani; Nasrullah Nasrullah (Institut Agama Islam Negeri Palopo, 2023)
A growing interest in studies about learners’ personalities in language learning has occurred from time to time. However, there are contradictions in many studies. Some claim that extroverts are more successful in language learning, whereas some believe the opposite. Other factors may influence the learner’s language learning, other than their personalities; therefore, this study explores the influence of extrovert and introvert personalities on language learning and the difference between them. The method used in this study is a literature review obtained from various research engine databases such as Google Scholar, ResearchGate, and ProQuest. The data are collected from journal articles, theses, dissertations, and books and analyzed using thematic analysis. This study found that various aspects influence the learner’s achievement in language learning other than the learner’s personality. The implication of this study benefits the teachers to define the best teaching method and strategy for each personality in language learning and the students to find the best learning strategy based on their personality. It also can be a reference for other researchers to conduct a study based on the same variables.